General and Electrophysiological Toxic Effects of Manganese in Rats following Subacute Administration in Dissolved and Nanoparticle Form - Edina Horváth; Zsuzsanna Máté; Szabolcs Takács; Péter Pusztai; András Sápi; Zoltán Kónya; László Nagymajtényi; András Papp (The Scientific World Journal)
In an attempt to model occupational and environmental Mn exposures and their possible interaction, young male Wistar rats were exposed to Mn by oral administration in dissolved form (MnCl2·4H2O, 14.84 and 59.36 mg/kg b.w.) and by intratracheal application of MnO2 nanoparticles (2.63 mg/kg b.w.). After 3 and 6 weeks oral, or 3 weeks oral plus 3 weeks intratracheal, exposure, general toxicological, and electrophysiological tests were done. Body weight gain was significantly reduced after 6 and 3 plus 3 weeks exposure, but the effect of the latter on the pace of weight gain was stronger. Organ weights signalized systemic stress and effect on lungs. Changes in evoked electrophysiological responses (cortical sensory evoked potential and nerve action potential) indicated that the 3 plus 3 weeks combined exposure caused equal or higher changes in the latency of these responses than 6 weeks of exposure, although the calculated summed Mn dose in the former case was lower. The results showed the importance of the physicochemical form of Mn in determining the toxic outcome, and suggested that neurofunctional markers of Mn action may indicate the human health effect better than conventional blood Mn measurement.